IbM KOTA MATARAM YANG MENGALAMI MASALAH SAMPAH RUMAH TANGGA - Sad Kurniati W.; Una Zaida; Pyo Apriliana Munawarah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2017)
Waste management that conventionally performed has brought a heavy burden on the government because it must provide many sufficient supporting infrastructure, as is also the case in the city of Mataram. Availability of infrastructure that used to transport waste from the source to get to the final disposal (landfill) is not sufficient so that they obtained a pile of trash on the roadside. On the other hand, a good waste management can produce useful products that have a selling value is to transform organic waste into compost or charcoal briquettes and inorganic waste into handicrafts. In this activity, fielded the devotion trying to empower communities in the Environment Monjok and Karang Sukun to manage waste household by establishing a bank of waste that can accommodate household waste produced by its citizens and turning it into useful products (compost / charcoal and craft) or sell to waste bank holding established the Environment Agency (BLH) Mataram.